Accruals intensity and auditor choice. Issue 3 (18th October 2019) - Aguir, Wael; Liu, Linxiao; Nwaeze, Emeka
Abstract : Purpose: The purpose of this paper is to examine the relationship between the intensity of accruals and auditor industry specialization. It investigates whether a client firm's accruals intensity is a factor associated with the firm being audited by an industry specialist auditor. Design/methodology/approach: This paper employs an empirical archival methodology using publicly available data. The sample consists of client firms that switched auditors from 2004 to 2014. Findings: The results show that accruals intensity is positively associated with the choice of an industry specialist auditor, measured both at the national and the city levels. These findings imply that companies with high levels of accruals choose an industry specialist auditor to signal the quality of their accruals and to gain more credibility for their financial reporting. Originality/value: This paper provides original empirical evidence of the association between accruals intensity and the choice of an industry specialist auditor. This link is new to the literature. Extant literature shows that firms with high levels of accruals are regarded as risky and suffer from reduced credibility in financial markets. This study contributes to the literature by showing that these firms choose an industry specialist auditor to alleviate investors' credibility concerns about the high levels of accruals. These findings provide insightful information to audit firms, to managers of firms that inherently display high levels of accruals and to the capital markets participants in general.